Early and long-term outcomes comparing neonates, infants, and preadolescents requiring extracorporeal membrane oxygenation for heart failure. (May 2020) - Sabashnikov, Anton; Merkle, Julia; Azizov, Farid; Djordjevic, Ilija; Eghbalzadeh, Kaveh; Tunggal, Irawati; Weber, Carolyn; Weixler, Viktoria; Rustenbach, Christian; Zeriouh, Mohamed; Kröner, Axel; Wahlers, Thorsten; et al.
Background: Application of extracorporeal membrane oxygenation in pediatric patients with severe heart failure steadily increases. Differentiation of outcomes and survival of diverse pediatric groups is of interest for adequate therapy. Methods: Between January 2008 and December 2016, a total of 39 pediatric patients needed veno-arterial extracorporeal membrane oxygenation support in our department. Patients were retrospectively divided into three groups: neonates (<30 days), infants (>30 days/<1 year), and toddlers/preadolescents (>1 year). Early outcomes as well as mid- and long-term survival up to 7-year follow-up were analyzed. Results: Basic demographics significantly differed in terms of age, height, and weight among the groups in accordance with the intended group categorization (p < 0.05). Survival after 30 days of extracorporeal membrane oxygenation application was equally distributed among the groups, and 44% of all patients survived. In terms of survival to discharge, no significant differences were found among groups. In total, 28% of patients survived up to 7 years. Infants were significantly more likely to undergo elective surgery (p < 0.001) and were predominantly weaned off extracorporeal membrane oxygenation, whereas need for urgent surgery (p < 0.001) was significantly higher in neonate group in comparison to other groups. Multinominal logistic regression analysis revealed significantly higher odds for need for re-exposure in infant group in comparison to toddler/preadolescent group as well as for incidence of neurological impairment of toddler/preadolescent group in comparison to neonate group (odds ratio = 14.67, p = 0.009 and odds ratio = 34.67, p = 0.004, respectively). Kaplan–Meier survival estimation analysis revealed no significant differences in terms of mid- and long-term survival among the groups (Breslow p = 0.198 and log-rank p = 0.213, respectively). Conclusion: Veno-arterial extracorporeal membrane oxygenation is a lifesaving therapeutic chance for pediatric patients in the setting of either failure to wean from cardiopulmonary bypass or failed resuscitation from cardiac arrest. A fair part of patients could be saved by using this technology. Survival rate among the groups was similar.